ANALISIS STRUKTUR BATIN PUISI “DI TOILET ISTANA” KARYA RADHAR PANCA DAHANA - Ahmad Hendra Komara; Tati Purwasih; Eli Syarifah Aeni (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the curiosity of research on the poetry of a Radhar Panca Dahana which makes poetry a vehicle for criticizing a political phenomenon that exists in the government. Politics and poetry are two things that are difficult to find correlation. Through this poem "Di Toilet Istana", the RDP crystallizes a political event that is deposited in arrays and stanzas, creating an ambiguity in meaning. The formulation of the problem of this research is how is the inner structure contained in the poem? The purpose of this study describes the inner structure, namely the theme, tone and feeling, atmosphere, and message. By focusing on analyzing his inner structure the researcher explores clearly and factually. The method used in this study is qualitative descriptive. The results of the analysis can be concluded that this poem is satire type which is packed with different perspectives, proven by the theme of political criticism, the tone offends the government world dramatically, the taste and atmosphere contained in the poem is full of irony, and the message conveyed means ambiguity for the reader.